The Study of User Acceptance Toward E-Learning System in Higher Education - Dana Indra Sensuse; Darmawan Baginda Napitupulu (Institute of Advanced Engineering and Science, 2017)
E-learning is a model of delivering learning content electronically with the help of computers and multimedia. ABC University has implemented the e-learning system for two (2) years in order to improve the quality of teaching and learning process. This study aims to determine the level of user acceptance, especially from the perspective of students. In other words, this study also wants to evaluate the implementation of e-learning systems in higher education as well as identifying any factors that encourage students to use e-learning system especially in ABC University. The research method used was survey with the approach of TAM (Technology Acceptance Model) as the technology acceptance evaluation model consisting of two main factors: perceived ease of use and perceived usefulness. The results showed perceived usefulness significantly positive influence on user acceptance, while perceived ease of use did not significantly influence on user acceptance. The perceived ease of use also significantly positive influence perceived usefulness. The variance of user acceptance could be explained by two factors about 50.5%.